Wages, Productivity, and Worker Characteristics: Evidence from Plant‐Level Production Functions and Wage Equations - Hellerstein, Judith K.; Neumark, David; Troske, Kenneth R. (Journal of Labor Economics, 1999)
We use a unique new data set that combines data on individual workers and their employers to estimate marginal productivity differentials among different types of workers. We then compare these to estimated relative wages, leading to new evidence on productivity‐based and nonproductivity‐based explanations of the determination of wages. Among our findings are (1) the higher pay of prime‐aged workers (aged 35–54) and older workers (aged 55+) is reflected in higher point estimates of their relative marginal products, and (2) for the most part, the lower relative earnings of women are not reflected in lower relative marginal products.